2014
DOI: 10.1038/ismej.2014.194
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of ammonia oxidizers and nitrite oxidizers to nitrification in four paddy soils

Abstract: Rice paddy fields are characterized by regular flooding and nitrogen fertilization, but the functional importance of aerobic ammonia oxidizers and nitrite oxidizers under unique agricultural management is poorly understood. In this study, we report the differential contributions of ammonia-oxidizing archaea (AOA), bacteria (AOB) and nitrite-oxidizing bacteria (NOB) to nitrification in four paddy soils from different geographic regions (Zi-Yang (ZY), Jiang-Du (JD), Lei-Zhou (LZ) and Jia-Xing (JX)) that are repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(97 citation statements)
references
References 59 publications
11
86
0
Order By: Relevance
“…These results were further supported by a study on different Chinese paddy soils where the AOA to AOB ratio varied from 22.9 to 667 [23]. A similar trend was observed in acidic paddy soils, where the pH ranged from 4.4 to 6.8 [27,29]. These findings are corroborated by the results of Chen et al (2011) [10], who found that AOA amoA genes outnumbered AOB amoA genes in acidic paddy soils.…”
Section: Abundance and Composition Of Aoa And Aobsupporting
confidence: 81%
See 3 more Smart Citations
“…These results were further supported by a study on different Chinese paddy soils where the AOA to AOB ratio varied from 22.9 to 667 [23]. A similar trend was observed in acidic paddy soils, where the pH ranged from 4.4 to 6.8 [27,29]. These findings are corroborated by the results of Chen et al (2011) [10], who found that AOA amoA genes outnumbered AOB amoA genes in acidic paddy soils.…”
Section: Abundance and Composition Of Aoa And Aobsupporting
confidence: 81%
“…This technique employs a pairwise comparison of 13 CO 2 (labeled microcosms) and 12 CO 2 (control treatment) to assess whether the 13 CO 2 is assimilated by ammonia oxidizers for autotrophic growth. The result of the DNA-based stable-isotope probing technique on paddy fields across southern China showed that AOA was more active in alkaline soils whereas AOB was more active in neutral soils [29]. However, the data on paddy soils from southwestern China [34] demonstrated that nitrification was mainly attributed to AOA in acidic soils, whereas AOB was mainly responsible for nitrification in alkaline soils.…”
Section: Aoa and Aob Contribution To Nitrificationmentioning
confidence: 72%
See 2 more Smart Citations
“…This ecological fitness and niche adaptation may have strongly supported the active cell division of the Nitrososphaera subcluster 1.1 in the CK and OF treatments, with soil pH values of 7.25 and 7.79 (Supporting Information Table S1) respectively. However, the lower richness of AOA in this study was likely due to our concentration solely on the active AOA and not on the overall community, an observation also made in other DNA-SIP studies (Xia et al, 2011;Wang et al, 2015a). However, the lower richness of AOA in this study was likely due to our concentration solely on the active AOA and not on the overall community, an observation also made in other DNA-SIP studies (Xia et al, 2011;Wang et al, 2015a).…”
Section: Effect Of Fertilization On the Composition Of Active Nitrifierssupporting
confidence: 69%